The Concept of Ecosystems Based on Digital Platforms: Benefits, Risks and Principles of Creation - Natalya N. MASYUK; Marina A. BUSHUEVA; Zinaida V. BRAGINA; Anna S. ILUKHINA; Aleksandr A. BOGOMOLOV (Communications of International Proceedings, 2022)
The digital economy, represented by new technologies, is rapidly developing and is increasingly being integrated into all spheres of the economy and society. The concept of ecosystems based on digital platforms is increasingly in demand by researchers to explain the processes taking place in the economy of enterprises, regions and countries in connection with the rapid development of digital technologies. This article is devoted to the conceptual foundations of the functioning of ecosystems based on digital platforms. It is noted that each platform is based on a very simple idea: to organize interaction between the producer and the consumer in the digital space. It has been convincingly proven that the modern economy is largely of an intermediary nature, since digital platforms carry the semantic load of organizing the interaction between suppliers and consumers. The expediency of the transition to the platform business and the inevitability of embedding in the ecosystem are argued. The risks of using platforms are identified. The principles of creating a platform business are formulated.
Keywords: digital platforms; ecosystems; platform business model; network effects.